The A–Z of Social Justice Physical Education: Part 2. Issue 5 (12th June 2020) - Landi, Dillon; Lynch, Shrehan; Walton-Fisette, Jennifer
Abstract : Education has the ability to both reproduce and transform broader social structures. Yet, teachers' responsibilities are constantly increasing whilst budgets, resources, and staffing are depleted. We argue that we are living in a time of great uncertainty and precarity. As physical educators, we should make attempts to be socially conscious of this precarity and provide equitable environments for all students. This article (the second installment of a two-part series) is an attempt to make an important step in enacting a socially just and informed physical education program. In so doing, we highlight specific ways that teachers and teacher educators can prepare for and teach about precarity in physical education. By providing resources, readings, and examples from practice, we provide a framework that promotes ethics of value, care, and zeal for others.